Aspects of blue economy in the Baltic Sea region - Pöntynen Riitta (Centrum Balticum Foundation, 2025)
Each sea basin has its specific features related to Blue Economy. This policy brief reflects the concept of
blue economy and its evolvement in the EU policies, and the specifics and relevance of blue economy in
the Baltic Sea region. Recent developments in blue economy policies are described with future prospects
of the main sectors: marine energy, maritime cluster, blue bioeconomy and maritime tourism. Blue
economy is integrated more deeply into policies to reduce emissions and decarbonization, most notably
aligned with the aims of EU’s Green Deal. Cross-sectoral cooperation is essential for development of blue
economy and Maritime Spatial Planning is an enabler towards sustainable blue economy and synergy
between the blue economy sectors. Case studies on blue economy, recent and ongoing projects with
blue economy topics, and drivers for future development will be presented as well as recommendations
based on these projects.